2020
DOI: 10.1016/j.stem.2020.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Adult Neural Stem Cell Niche Proteome Identifies Key Regulators of Adult Neurogenesis

Abstract: Highlights d Proteomics define the NSC niche-specific extracellular matrix d Detergent-solubility profiling reveals extracellular matrix architecture d Transglutaminase 2 regulates neurogenesis d Stiffness is increased in the neurogenic niches of the brain

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
98
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(118 citation statements)
references
References 108 publications
(155 reference statements)
9
98
0
Order By: Relevance
“…In our investigation of the adult neurogenic niche (Kjell et al, 2020), also using the QDSP protocol, we found that ECM proteins, such as Tn-C, are more soluble compared to the brain parenchyma. Tn-C is also highly soluble in the scar region analyzed by QDSP at 28 dpi here, which is opposite to its insoluble nature in lung injury and atherosclerotic plaques (Schiller et al, 2015;Wierer et al, 2018).…”
Section: Monocyte-dependent Ecm In the Glial Scarmentioning
confidence: 77%
See 3 more Smart Citations
“…In our investigation of the adult neurogenic niche (Kjell et al, 2020), also using the QDSP protocol, we found that ECM proteins, such as Tn-C, are more soluble compared to the brain parenchyma. Tn-C is also highly soluble in the scar region analyzed by QDSP at 28 dpi here, which is opposite to its insoluble nature in lung injury and atherosclerotic plaques (Schiller et al, 2015;Wierer et al, 2018).…”
Section: Monocyte-dependent Ecm In the Glial Scarmentioning
confidence: 77%
“…We also see changes in the solubility of synaptic proteins (e.g., Gria2-3, Olfm3, Glgap1, and Vamp1), while we did not see an obvious change in the solubility of PNN proteins in the scar stage between the genotypes. Our previous QDSP analysis of PNN proteins in the uninjured cerebral cortex had revealed that they are typically not insoluble (in fraction 4), but rather belong to a less detergent resistant category (fractions 2-3; Kjell et al, 2020). Taken together, lack of monocyte invasion affects ECM proteins in a long-term manner toward a state closer to the un-injured contralateral site, thus normalizing the scar ECM.…”
Section: Monocyte-dependent Ecm In the Glial Scarmentioning
confidence: 96%
See 2 more Smart Citations
“…45 It cross-links fibronectin and has scaffolding functions with integrin β1, both of which are associated with radiation resistance and stemness, 46,47 and has recently been proposed to promote neurogensis from neural stem cells in the adult brain. 48 Its inhibition improved survival in a glioma xenograft model 49 and it has been shown to be a prognostic indicator of shorter time to relapse after chemoradiotherapy. 50 We first confirmed increased expression of TGM2 in matrix from multiple batches of astrocytes from different individuals by western blot (Fig 5B).…”
Section: Irradiated Astrocytes Secrete Tgm2 In Vitro and In Vivo Aftementioning
confidence: 99%